Pre-treatment of oil palm biomass for fermentable sugars production - Ahmad Rizal, Nur Fatin Athirah; Ibrahim, Mohamad Faizal; Zakaria @ Mamat, Mohd Rafein; Abd. Aziz, Suraini; Phang, Lai Yee; Hassan, Mohd Ali (MDPI, 2018)
Malaysia is the second largest palm oil producer in the world and this industry generates more than 80 million tonnes of biomass every year. When considering the potential of this biomass to be used as a fermentation feedstock, many studies have been conducted to develop a complete process for sugar production. One of the essential processes is the pre-treatment to modify the lignocellulosic components by altering the structural arrangement and/or removing lignin component to expose the internal structure of cellulose and hemicellulose for cellulases to digest it into sugars. Each of the pre-treatment processes that were developed has their own advantages and disadvantages, which are reviewed in this study.